Impact of cultural diversity and power concentration on urban regeneration with the moderating effect of feudalism - Ijaz, Rabbiya ( 130005) 2016 (Islamabad Air University School of Management AUSOM ( Air University Main Campus), 2016)
Today$1 (Bs business world is dramatically changing with the changing people$1 (Bs personalities and behavior patterns. This change in the personalities is thus based by the distinct future preferences for place to live and to develop. Thus there is an increased trend of urban Regeneration. Urban regeneration is a process of development that focuses on the clearance of old; not used or misused area of a particular region followed by a relatively new and developed area which is a result of huge investment in the form of people and money. This research study thus highlights the effect of cultural diversity and power concentration on urban regeneration. The model studies various factors that influence urban regeneration and the effect of cultural diversity and power concentration over urban regeneration in the presence of wide concept of feudalism. Data is taken from the few regions of Punjab, Pakistan namely Jhung and dera ismael khan by applying reliability, correlation and regression analysis. . Findings of study suggest that cultural diversity and power concentration significantly affect urban regeneration whereas feudalism have insignificant role in the whole process.s
BBA